Freedom and Outrage in Art Education - Lankford, E. Louis (Journal of Aesthetic Education, 1994)
Publisher: University of Illinois Press
Keywords: Myriam

Sexual Harassment of Women Journalists - Walsh-Childers, Kim; Chance, Jean; Herzog, Kristin (Journalism & Mass Communication Quarterly, 1996)
A survey of 227 women newspaper journalists revealed that more than 60 percent believe sexual harassment is at least somewhat a problem for women journalists; more than one-third said harassment has been at least somewhat a problem for them personally. Two-thirds experience nonphysical sexual harassment at least sometimes, and about 17 percent experience physical sexual harassment at least sometimes. News sources were the most frequent harassers, and harassment ranged from degrading comments to sexual assault._
Publisher: SAGE Publications Inc
Keywords: Journalisme; Myriam; journalism